STRATEGI PENGEMBANGAN DESA WISATA BERKELANJUTAN DI DESA PARE MAS KECAMATAN JEROWARU - Eldiranata, Iswa; Nessa, Syarifa Helnia; Mulajati, Mardiansa Rohana; Khotimah, Amalia Nurul; Rizki, M. Syakroni; Rizal, Muhammad Khairul; Qomariah, Qomariah; Haryani, Ni Made Astiti; Maryam, Indah; Rahma, Nurhadijah (Jurnal Wicara, 2025)
Pare Mas Village, Jerowaru District, East Lombok, has great potential in developing mangrove-based ecotourism, but its current condition is starting to fade. The mangrove tourism destination of Pare Mas Village needs further restoration and development, not only to attract tourists to visit, but also as a form of community maintenance of their village tourism area. By implementing the right strategy, Pare Mas Village has a great opportunity to become a leading ecotourism destination in East Lombok. This KKN PMD Unram aims to revive the mangrove tourism destination of Pare Mas Village by implementing a sustainable village development strategy, helping to promote tourist villages through social media, and socializing the strengthening of village tourism institutions. The data collection method uses observation and interviews, with the aim of obtaining information about Pare Mas Village. With the implementation stage of the activity divided into 3 important parts, namely observation and planning, socialization, and the provision of tours and promotion of Pare Mas Village tourism, the socialization activity of strengthening village tourism institutions is in line with the main objective of the KKN PMD activity to revive the tourism sector of Pare Mas Village which is starting to fade, and all of that begins with strengthening village tourism institutions. This received a positive response from the Pare Mas Village community, which then became a driver in reviving the tourism sector of Pare Mas Village, as well as village MSMEs. Empowerment of Village Communities was given the opportunity to participate in the One Day Trip to Pesona Desa Pare Mas tourism activity, such as becoming a tour guide to selling typical Pare Mas Village products. Tourism promotion was also held by reviewing the tourism potential in Pare Mas Village, including famous tourist attractions in Pare Mas Village to attract visitors. Overall, the KKN PMD program was successfully implemented and had a positive impact on the Pore Mas Village community, both in terms of economy, tourism, and environmental awareness. With the assistance and follow-up programs, it is hoped that the community can manage their local potential independently and sustainably, making the village more independent, creative, and competitive